Sustainability at HEIs: Mapping Good Practice. - Asikainen, Eveliina; Eskola-Salin, Nina; Fischer, Sophie; Giedraitiené, Vytaute; Beseckas, Povilas; Mairhofer, Stephanie; Köder, Lea; Schmitt, Jan; Walter, Holger; Guerrero-Pérez, María Olga; Blázquez-Parra, Elidia Beatriz; Bikuviené, Ina; et al. (Technische Hochschule Würzburg-Schweinfurt, 2024)
Global climate change is a cognitive challenge for many people and often evokes negative associations due to its complexity and interactions with politics, social movements and economic developments. Therefore, the possession of green skills becomes central to the fight against climate change. The European Council conclusions recognize this urgency and underline the need for a transition to green skills. This recognition also extends to higher education, where institutions have a crucial role to play in tackling the climate crisis. Personal Green Skills in Higher Education (PeGSinHE) is an Erasmus+ KA2 project coordinated by Kauno Kolegija (KK, Lithuania), Tampere University of Applied Sciences (TAMK, Finland), Hochschule für Agrar- und Umweltpädagogik (HAUP, Austria), Universidad de Málaga (UMA, Spain) and Technical University of Applied Sciences Würzburg-Schweinfurt (THWS, Germany). The strategically designed project aims not only to promote green skills among students and encourage personal behavioral change in line with the Sustainable Development Goals, but also to instill a sense of social responsibility in the partner institutions. The focus is on empowering lecturers at partner universities through innovative teaching and learning methods to effectively impart green skills to students. This report describes the objectives and methodology used to assess environmental and sustainability competencies in the higher education institutions involved in the project.
Keywords: Educación ambiental; Enseñanza superior; Cambios climático; HEI